â€œRefuel your futureâ€: Asphalt Afrofuturism and the Slow Violence of Water and Oil in Nnedi Okoraforâ€™s Lagoon by Gemma Field - Field, Gemma (WritingThreeSixty, 2018)
This paper outlines a petrocritical reading of Nnedi Okorafor’s Lagoon, an Afrofuturist tale of alien invasion of Lagos, Nigeria. Petrocriticism, originally the study of the oil encounter in literature that has widened to include all aspects – political, economic, aesthetic, phenomenological, etc. – of its representation, is helpful in discussing Nigerian texts. Nigeria is one of the world’s biggest producers of oil, and like many other countries endowed with black gold, has a dubious colonial history has become in the postcolonial present what Rob Nixon refers to as the ―resource curse‖. Beyond the adverse environmental consequences of oil, it is implicated in political trickery in the West and despotism elsewhere, what Timothy Mitchell describes as ―carbon democracy‖. Nevertheless, it is fundamental to everyday life, so Imre Szeman uses the term ― petromodernity. Lagoon problematises this condition from its first page when a swordfish imbibed with alien powers attacks an offshore oil rig, a tension that culminates in the Bone Collector, the man-eating motorway – the physical manifestation of the text’s preoccupation. Alongside the novel’s aliens are elements of urban fantasy – the road monster predates the aliens (and Lagos) - and mythology, utilising icons from Nigerian folklore. The Bone Collector is only sated when it consumes an alien, pointing to the impossibility of an indigenous solution to the issues raised by the text. Okorafor’s combination of these elements attempts to resolve the text‘s oil-based anxiety - to imagine what Gerry Canavan calls ―petrofuture speaks to Nigeria‘s political difficulty in extricating itself from the iniquitous structures of petro-imperialism.